Designing web-based designed for decision making process of upgrading slum sanitation - Apriadi Dian Permatasari; Barjenbruch Matthias; Soewondo Prayatni (E3S Web of Conferences, 2024)
In Indonesia’s slum areas, Inadequate sanitation is a major challenge. This study introduces an interactive web-based platform, UPSS (“Upgrading Slum Sanitation”), to aid in selecting appropriate sanitation technologies for these regions. UPSS integrates a Decision Support System (DSS) to streamline the decision-making process. Our objective was to create UPSS to facilitate the selection of suitable sanitation technologies, tailored to the specific needs of Indonesia slum areas. We employed a mixed-methods approach to develop UPSS, focusing on user-friendly interfaces and streamlined decision-making processes. The first screen will help identify the slum classification (high, middle and low slum) by using the questionnaire. The following screens will identify alternative sanitation technologies. After that we apply the UPSS in the case study area, Manado Indonesia. The application of UPSS in slum areas of Indonesia demonstrated its effectiveness in reducing planning time for sanitation improvement. The results, presented in an easily interpretable format, showed a range of sanitation options and were well-received by facilitators in these areas. UPSS proves significant in improving sanitation planning in slums. It offers a quick, efficient, and user-friendly tool for stakeholders to identify and implement the most suitable sanitation technologies, thereby addressing a critical need in urban sanitation management